2021
DOI: 10.1051/e3sconf/202124408024
|View full text |Cite
|
Sign up to set email alerts
|

Minimization of the automatic machine structure process of accounting and control of railway automation and telemechanics devices

Abstract: The article explores the features of electronic document management of technical documentation of railway automation and telemechanics. A block diagram of an automaton model of technical documentation is developed. The proposed block diagram of a formalized model of technical documentation consists of matrices of external microoperations, internal microoperations, code creation for the following microcomponents. The number of internal states of the firmware is completely determined by the number of logic eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…When supplying rail traffic in scenarios with very poor reliability, these systems are prone to errors. Small errors might result in significant financial losses and occasionally even deadly mishaps [14][15][16][17][18][19][20][21]. Thus, the safety degree of automation and remote control systems that guarantee the security of train movement should be examined.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When supplying rail traffic in scenarios with very poor reliability, these systems are prone to errors. Small errors might result in significant financial losses and occasionally even deadly mishaps [14][15][16][17][18][19][20][21]. Thus, the safety degree of automation and remote control systems that guarantee the security of train movement should be examined.…”
Section: Methodsmentioning
confidence: 99%
“…The route setting based on the artificial neural network model [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] is shown in Figure 1, accounting for the train's moving stations. We will construct the neuron set in two layers in this instance [34][35].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Every station has many pairs of control points installed on the approach section. It is found that the intervals between these locations correspond to the electrical centering system's mode entry times [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. When the rolling stock approaches the station, the first of the two control points notifies the interlocking system.…”
Section: Time Indicators For Automatic Preparation Of Routes For Trai...mentioning
confidence: 99%
“…2, a -For high-speed trains, the following expressions (4), ( 5), (6), and ( 7) are used to calculate the distance between the first and second control points in the figure as well as the rolling stock's time of movement. High-speed train braking times are expressed as follows: (4) for high-speed train braking times between 0 and 108 km/h, (5) for high-speed train braking times between 108 and 350 km/h, and ( 6) and ( 7) when braking is an expression of the path [15][16][17][18][19][20][21][22][23][24].…”
Section: Time Indicators For Automatic Preparation Of Routes For Trai...mentioning
confidence: 99%